INOVAŢIA ÎN MANAGEMENT – RESPONSABILITATEA MANAGERILOR. PROVOCĂRI, GÎNDURI ŞI ÎNDEMNURI - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The article is about the innovation in management and the changes producing in the institutional communication, in the library structure (the example of the Municipal Library B.P. Hasdeu). The author highlights the most striking innovative services and practices offered by the library, presents the studies and the investigations fulfilled by the librarians, formulates the problem of the management of innovation and the manager flexibility.